WOMEN IN CARCERE AND ADULT EDUCATION - Maria Cristina Silva; Carmem Lucia Eiterer (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article is part of our study conducted in the doctorate. We have divided the text in three stages as follows: the first a brief contextualization on female prisons and women in jail, at second stage, I present short stories of five women living in the prison in which I try to bring their everyday lives lived in the prison and in the last step I tract of the relationship of these detainees with the school and the schooling processes. At the end I trace some considerations and final questions about women in prison.